1997
DOI: 10.1099/0022-1317-78-8-2113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a subgroup I geminivirus from a legume in South Africa.

Abstract: A South African geminivirus for which we propose the name bean yellow dwarf virus (BeYDV) has been isolated from French bean (Phaseolus vulgaris cv. Bonus) showing stunting, chlorosis and leaf curl symptoms. A full-length cloned copy of the viral genome produced characteristic symptoms of the disease when reintroduced into French bean by agroinoculation, and was systemically infectious in Nicotiana benthamiana, N. tabacum, Lycopersicon esculentum, Datura stramonium and Arabidopsis thaliana. BeYDV resembles sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…Sequence analysis of the full-length amino acid sequence of the putative Rep of SsHADV-1 showed that it shares the highest sequence identity with the Reps of chickpea chlorotic dwarf virus (25), bean yellow dwarf virus (26), and tobacco yellow dwarf virus (27) (Table S2). These three viruses that infect dicotyledonous plants belong to the genus Mastrevirus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of the full-length amino acid sequence of the putative Rep of SsHADV-1 showed that it shares the highest sequence identity with the Reps of chickpea chlorotic dwarf virus (25), bean yellow dwarf virus (26), and tobacco yellow dwarf virus (27) (Table S2). These three viruses that infect dicotyledonous plants belong to the genus Mastrevirus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, previously studied, tandem repeat infectious clones of (Stanley et al, 1986) and BeYDV-[ZA : Mpu : 94] (BeYDV; Y11023) (Liu et al, 1997).…”
Section: Hanleymentioning
confidence: 99%
“…(Morris et al, 1992;Horn et al, 1993). Albeit Bean yellow dwarf virus (BeYDV) (Liu et al, 1997a) (infect dicotyledonous plants) presence has been recorded in both Pakistan and South Africa (Halley-Scott et al, 2007). However, Thomas et al (2010) reported Chickpea chlorosis virus (CpCV-A, CpCV-B) and Chickpea redleaf virus (CpRLV) from Australia.…”
Section: Turnip Curly Topmentioning
confidence: 99%